2013
DOI: 10.15282/ijame.8.2013.8.0096
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Recirculation Zone and Ignition Position of Non-Premixed Bluff-Body for Biogas MILD Combustion

Abstract: Combustion ignition study is important due to the combustion process becoming more lean and efficient. This paper studied the recirculation zone and ignition location for the bluff-body non-premixed MILD burner with biogas used as fuel. The location of the ignition was critical to ensure that the spark energy supply during the ignition process can successfully ignite the mixture of air and fuel. The numerical calculations were done using the commercial code ANSYS-Fluent to simulate the furnace with a bluffbody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Moreover, computational simulation frequently provides information on physical quantities that are difficult to measure. CFD is increasingly being used for the optimization of gas burners (Scharler & Obernberger, 2000) and industrial gas furnaces (Dally, Riesmeier, & Peters, 2004;Noor et al, 2013a;Riahi, Mergheni, Sautet, & Nasrallah, 2012) or coal combustion (Calchetti, Nardo, Mongibello, & Mongiello, 2007). In this study, the CFD was used to model MILD combustion in the mode of non-premixed combustion.…”
Section: Cfd Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, computational simulation frequently provides information on physical quantities that are difficult to measure. CFD is increasingly being used for the optimization of gas burners (Scharler & Obernberger, 2000) and industrial gas furnaces (Dally, Riesmeier, & Peters, 2004;Noor et al, 2013a;Riahi, Mergheni, Sautet, & Nasrallah, 2012) or coal combustion (Calchetti, Nardo, Mongibello, & Mongiello, 2007). In this study, the CFD was used to model MILD combustion in the mode of non-premixed combustion.…”
Section: Cfd Simulationsmentioning
confidence: 99%
“…Nakamura, Smart, and Van de Kamp (1993) and (Weber, Orsino, Lallemant, & Verlann, 2000;Weber, Smart, & Kamp, 2005) experimentally studied pilot-scale furnaces equipped with heat exchangers and demonstrated that heat transfer was affected by the port locations and angles. After finalizing the pre-design, the simulation was done on the final model (Figure 2) for the ignition location study (Noor et al, 2013a), air fuel ratio study (Noor et al, 2012b) and other parametric studies (Noor et al, 2012c) on the MILD combustion using biogas as a fuel. Different combinations of air and fuel compositions injected into the chamber gave different results.…”
Section: Cfd Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Homogeneous charge compression ignition (HCCI) engines have received increasing attention recently because of their advantages in reducing emissions levels, such as NOx [1][2][3][4][5][6]. An attempt by regulatory bodies, such as those in Europe, the United States (US) and Japan, to reduce emissions levels from conventional engines [7][8][9] has made the HCCI engines a viable alternative for low emissions engines.…”
Section: Introductionmentioning
confidence: 99%
“…A new combustion process is able to contribute to the increase of combustion thermal efficiency and reduce of the emissions. MILD combustion produces higher thermal efficiency due to re-cycling of Exhaust Gas by using exhaust gas recirculation (EGR) [7,[9][10][11][12]. Others call it flameless oxidation (FLOX) [13,14], High-Temperature Air Combustion (HiTAC) [15,16] and Colourless Distributed Combustion (CDC) [17,18].…”
Section: Introductionmentioning
confidence: 99%